The care and transport of trauma victims by layperson emergency medical systems: a qualitative study in Delhi, India - Kavi Bhalla; Veena Sriram; Radhika Arora; Richa Ahuja; Girish Agrawal; Geetam Tiwari; Dinesh Mohan (BMJ Global Health)
Introduction Ambulance-based emergency medical systems (EMS) are expensive and remain rare in low- and middle-income countries, where trauma victims are usually transported to hospital by passing vehicles. Recent developments in transportation network technologies could potentially disrupt this status quo by allowing coordinated emergency response from layperson networks. We sought to understand the barriers to bystander assistance for trauma victims in Delhi, India, and implications for a layperson-EMS.Methods We used qualitative methods to analyse data from 50 interviews with frontline stakeholders (including taxi drivers, medical professionals, legal experts and police), one stakeholder consultation and a review of documents.Results Respondents noted that most trauma victims in Delhi are rapidly brought to hospital by bystanders, taxis and police. While ambulances are common, they are primarily used for interfacility transfers. Entrenched medico-legal practices result in substantial police presence at the hospital, which is a major source of harassment of good Samaritans and interferes with patient care. Trauma victims are often turned away by for-profit hospitals due to their inability to pay, leading to delays in treatment. Recent policy efforts to circumscribe the role of police and force for-profit hospitals to stabilise patients appear to have been unsuccessful.Conclusions Existing healthcare and medico-legal practices in India create large systemic impediments to improving trauma outcomes. Until India’s ongoing health and transport sector reforms succeed in ensuring that for-profit hospitals reliably provide care, good Samaritans and layperson-EMS providers should take victims with uncertain financial means to public facilities. To avoid difficulties with police, providers of a layperson-EMS would likely need official police sanction and carry visible symbols of their authority to provide emergency transport. Delhi already has several key components of an EMS (including dispatcher coordinated police response, large ambulance fleet) that could be integrated and expanded into a complete system of emergency care.